Pharmacogenetics-based population pharmacokinetic analysis of tenofovir in Thai HIV-infected patients - Kanokrat Rungtivasuwan (2018)
© 2017 Future Medicine Ltd. Aim: To develop a population pharmacokinetic model and identify sources of variability, genetic and nongenetic factors, of tenofovir. Methods: The ABCC2 and ABCC4 polymorphisms were genotyped in 342 patients. A nonlinear mixed effects model was used to develop the population pharmacokinetic model and investigate the influence of these polymorphisms and other patient specific covariates on the pharmacokinetics of tenofovir. Results: The estimated glomerular filtration rate calculated by the Cockcroft and Gault equation, concomitant use of lopinavir/ritonavir and ABCC4 3463A>G polymorphism were associated with tenofovir apparent oral clearance (CL/F). The use of lopinavir/ritonavir decreased tenofovir CL/F by 25%. Patients carrying ABCC4 3463 AG or GG had a tenofovir CL/F 11% higher than those with genotype AA. Conclusion: Renal function, co-medication and genetic variation impact the pharmacokinetics of tenofovir. These factors should be taken into consideration to guide the individual tenofovir disoproxil fumarate dosage regimen in Thai HIV-infected patients.